Light and transmission electron microscopy of generalized dystrophic epidermolysis bullosa (Pasini's albopapuloid subtype) Microscopia óptica e eletrônica de transmissão da epidermólise bolhosa distrófica generalizada (subtipo albo-papulóide de Pasini) - Hiram Larangeira de Almeida Jr; Lísia Nudelmann; Nara Moreira Rocha; Luis Antonio Suita de Castro (Sociedade Brasileira de Dermatologia, 2012)
Pasini's albopapuloid epidermolysis bullosa is a very rare subtype of generalized dystrophic dominant epidermolyis bullosa. A 30 year-old white female patient presented since her childhood disseminated small blisters and papules. Light microscopy of a blister showed dermal-epidermal cleavage; moreover, focal areas of dermal-epidermal splitting were also observed. Transmission electron microscopy also identified focal areas of cleavage, which were seen below the lamina densa. It is important to recognize this condition as a variant of epidermolysis bullosa, since the most important cutaneous findings are generalized papules and not blisters and erosions as in other forms of epidermolysis bullosa. A epidermólise bolhosa albo-papulóide de Pasini é uma variante rara da forma generalizada de epidermólise bolhosa distrófica dominante. Uma paciente de 30 anos apresenta desde a infância pápulas e bolhas disseminadas. A microscopia óptica de uma bolha demonstrou clivagem dermo-epidérmica; além disso áreas focais de desprendimento dermo-epidérmico foram encontradas. A microscopia eletrônica de transmissão identificou a clivagem abaixo da lâmina densa. É importante que se reconheça essa variante de epidermólise bolhosa, já que o aspecto clínico predominante são pápulas disseminadas e não bolhas como nas outras formas de epidermólise bolhosa.